The Implementation of the Hierarchical Hazard Control Model to Assess the Respiratory Protection of Quarry and Allied Workers in Namibia - Saima Shihepo; Roswitha Mahalie; Omotayo Awofolu (Geography, Earth Science and Environment: Research Highlights Vol. 9, 2025)
The increased risks of adverse respiratory outcomes among quarry and allied workers are affected by high levels of cumulative dust exposure, which is a significant concern in the occupational health sector in developing countries, like Namibia. The study examines respiratory protection practices among quarry and allied workers in Namibia, amidst rising concerns over occupational respiratory disorders due to prolonged exposure to respirable dust. Using the Hierarchical Hazard Control Model, the study assessed the Engineering Controls, Administrative Controls, Educational/Training Programmes, and Medical Surveillance Measures in dust controls for 304 quarry and allied workers in the Erongo, Otjozondjupa, and Kunene regions. This study used self-administered questionnaires to collect data from the quarry and allied workers, between November and December 2022. A Chi-square (X2) test was used to determine the association between the level of employee respiratory protection and individual factors significant at p=0.000. Findings showed a statistically significant association between employee respiratory protection and employment status (X2(1) = 7.592, p = 0.000), job category (X2(9) = 37.742, p = 0.000), educational level (X2(3) = 68.517, p = 0.000) and worksite (X2(8) = 282.178, p = 0.001). A strong positive correlation between worksite and respiratory protection (r=0.7, p<0.01), negative correlation between worksite protection and education/training programs (r=0.841, p<0.05) was found. The findings underscore a critical gap in implementing effective engineering controls and training programs, increasing the risk of respiratory illnesses among workers. In conclusion, the study revealed that quarry and allied workers could not effectively implement engineering controls to reduce workers’ exposure to respirable dust due to the lack of an occupational respiratory health framework, safety regulations and enforcement, and education and training. The study also provided evidence that most allied and quarry workers did not undergo the mandatory medical examination, as a request of limited hazard control measures. Recommendations include a need for an occupational respiratory health framework for quarry and allied workers to ensure occupational respiratory health. Effective government policy that will enhance occupational safety and health in mining and quarrying is necessary for accident prevention in Namibia.